2006
DOI: 10.1007/s11010-006-9167-x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus replication causes oxidative stress in HepAD38 liver cells

Abstract: HBV replication modulates host gene expression and induces oxidative stress. In this HepAD38 model early events (0-4 days) in the host cell after induction of HBV replication can be studied under strictly defined conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 24 publications
4
46
0
2
Order By: Relevance
“…Valgimigli et al reported that ROS levels in HBV chronic hepatitis patients were higher than in healthy controls by radical probe electron paramagnetic resonance measurements of human liver biopsy specimens (41). In addition, induction of HBV replication in human hepatoma HepAD38 cells, in which HBV production is under the control of a tetracycline-regulated promoter, led to up-regulation of genes related to oxidative stress (42). The fact that the liver histopathology (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Valgimigli et al reported that ROS levels in HBV chronic hepatitis patients were higher than in healthy controls by radical probe electron paramagnetic resonance measurements of human liver biopsy specimens (41). In addition, induction of HBV replication in human hepatoma HepAD38 cells, in which HBV production is under the control of a tetracycline-regulated promoter, led to up-regulation of genes related to oxidative stress (42). The fact that the liver histopathology (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…1). There have been many studies on oxidative stress production by HBV using HBV-Tg mice or HBV DNA transfection [1,33]. Reactive oxygen species (ROS) such as superoxide, hydrogen peroxide, as well as hydroxyl radical may damage cellular macromolecules [34].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the previous study that HBVinduced ROS can cause HCC [3,4,14] and the expression level of Hsp90 is elevated in HCC tumor tissue [15], we hypothesized that ROS might improve Hsp90-driven HBV production. In this research, we exploited cell-free system and HepG2.2.15 cells to test the functional significance of ROS in Hsp90-driven HBV capsid formation.…”
Section: Introductionmentioning
confidence: 99%